Echocardiographic Features of Evolving Aortic Root Abscess - Khan, Mohsin (JACC Case Rep, 2019)
Paravalvular abscess is a serious complication of endocarditis that often requires surgical intervention. Diagnosis is achieved by recognizing echocardiographic features of paravalvular abscess seen on transesophageal echocardiography. Our case report highlights these features seen in a patient with aortic root abscess and aortotricuspid annulus involvement. (Level of Difficulty: Beginner.)